2002
DOI: 10.1080/1071576021000016472
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of α-tocopherol-succinate (Provitamin-E) in Cyclophosphamide Induced Testicular Gametogenic and Steroidogenic Disorders: A Correlative Approach to Oxidative Stress

Abstract: The present study was undertaken to find out the adverse effects of cyclophosphamide on testicular activities along with testicular oxidative stress at its therapeutic dose and the protective effects of alpha-tocopherol succinate on testicular dysfunctions induced by cyclophosphamide in mature albino rats. A significant diminution in the activities of testicular delta 5, 3 beta-hydroxysteroid dehydrogenase (HSD) and 17 beta-hydroxysteroid dehydrogenase (HSD) along with significant reduction in the plasma level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 41 publications
8
61
1
Order By: Relevance
“…In our study, the lower sperm concentration and the lower number of motile sperm in the DM group are consistent with the reproductive disorders [45,46] . Present findings with decreased sperm concentration in diabetic rats were similar to those of Bal et al [4] , while being slightly lower than those of Navarro-Casado et al…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, the lower sperm concentration and the lower number of motile sperm in the DM group are consistent with the reproductive disorders [45,46] . Present findings with decreased sperm concentration in diabetic rats were similar to those of Bal et al [4] , while being slightly lower than those of Navarro-Casado et al…”
Section: Discussionsupporting
confidence: 88%
“…Singh et al [40] reported that the decrease in sperm density may be related to the decrease in the number of Leydig cells [4] . Some authors reported that the reduced epididymal and motile sperm concentrations in diabetic rats could arise from a combined effect of decreased Leydig cell function and the oxidative stress induced by diabetes [4,46,48,49] . It has been shown that the destructive effect of free oxygen radicals reduces the sperm motility and viability [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh et al stated that the difference in the testosterone level between cyclophosphamide-treated and control animals served as evidence for the damage of the testes. 7 Also, these data were strengthen the idea about the inhibitory effect of cyclophosphamide on testicular steroidogenesis and spermatogenic disorder indicated by diminution in the number of different generation of germ cells.…”
Section: Anan Hh Et Al Int J Sci Rep 2017 Feb;3(2):39-48supporting
confidence: 65%
“…Moreover, the oxidative damage to this poly-unsaturated fatty acid of the cell membrane results in impairment of membrane fluidity and permeability. 7 As other chemotherapeutic drugs, cyclophosphamide has variable hazards that either persist or relief spontaneously. Few literatures were done upon the effect of cyclophosphamide on the male and female gonads and how long it persists.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E has also been shown to suppress lipid peroxidation in testicular microsomes and mitochondria 36,37 and to reverse the detrimental effects of oxidative stress on testicular function mediated by exposure to such factors as ozone, iron overload, intensive exercise or exposure to aflatoxin, PCB, cyclophosphamide and formaldehyde. 28,32,33,[38][39][40][41][42] Furthermore testicular vitamin E levels have also been shown to fall significantly when oxidative stress is induced by exposure to pro-oxidant stimuli such as chromium. 34 Although catalase is of limited importance in the testes, there are several isoforms of GPx in this tissue that use glutathione (GSH) as a source of electrons to reduce H 2 O 2 to water.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%